Opportunities for the Application of Zakat as a Deduction for Individual Taxable Income as an Alternative Fiscal Policy in Indonesia - Fuhairah, Muhammad Tiar Fuhairah; Herianingrum, Sri (El-Qist: Journal of Islamic Economics and Business (JIEB), 2024)
This study aims to explore the feasibility of implementing zakat as a deductible component from individual taxable income, proposing it as an alternative fiscal policy for Indonesia. Employing a qualitative descriptive method with a library research approach, this research analyzes regulatory frameworks, fiscal policies, and zakat potential in Indonesia. The findings reveal that Indonesia's substantial Muslim population—87.02%—combined with the consistent 30.02% annual growth in zakat collection, presents a significant opportunity to institutionalize zakat as part of the national fiscal framework. Integrating zakat into the tax system could alleviate the dual financial burden on Muslim taxpayers while simultaneously enhancing fiscal equity and social welfare. The specific contribution of this research to the international discourse lies in offering a practical model for harmonizing religious financial obligations with modern taxation systems in Muslim-majority countries. It provides empirical insights and policy recommendations applicable to other nations seeking to leverage faith-based financial instruments within formal fiscal systems.